TRAUMA HEALING PASCABENCANA PADA ANAK-ANAK KORBAN GEMPA BUMI MELALUI PELATIHAN DA SUMINAGASHI (MELUKIS DI ATAS AIR) DI DESA REMBUN, KECAMATAN DAMPIT KABUPATEN MALANG - Siti Sumarsih; Anita Kurnia Rachman; Susandi Susandi (JPM PAMBUDI, 2021)
Community service carried out by Lecturer of Indonesian Language and Literature Education Study Program, IKIP Budi Utomo aims to help children affected by the earthquake to reduce trauma healing through playing activities and painting on water. The implementation method used in this activity is the method of playing and painting together on water (da suminagashi). Trauma Healing is a situation where children feel fear, anxiety, and fear due to events, accidents, natural disasters that have been experienced. This activity was carried out for three days and in collaboration with the Omdobara Command Post in Rembun Village, Dampit District, Malang Regency. This service activity is also assisted by four coordinators at the Omdobara Command Post who are used to interacting with children every day. The results of this activity, which can help parents and children in reducing the trauma caused by the earthquake that occurred a few months ago. Another result is that children can play and learn to paint on water together so that children can be happy again.